Critical Thinking Development Program in EFL learning - CARTES, NINETTE; LARENAS, M. EDITH; PEREIRA, YASNA (Paideia Revista de Educación, 2020)
This is an experimental and quantitative study in the field of Linguistics applied to education attempts to determine the influence of the Critical Thinking Development Program, through a conference-like course aided by computers, on learning styles, linguistic competences, types of thinking, and the activation of intelligence, over one semester. Specifically, this study tries to prove that learning styles exert a certain influence on critical thinking, as well as on linguistic competences, emotional intelligences and leadership abilities. Hence the methodology is based on the cognitive paradigm which helps university learners develop Constructivist and Interactionist strategies to obtain information in the computer lab in order to generate and construct their own learning and knowledge. The sample of 20 university students studying English as L2 was exposed to the computer to obtain information about a specific topic to be analyzed and presented orally in the group, and in writing. Students had to develop collaborative learning with their classmates to eventually construct knowledge. In addition, values and attitudes were internalized and reinforced, and the CHAEA Questionnaire was used to establish the types of learning styles students used at the beginning and at the end of the semester. Results from the statistical data obtained in Pre-tests and Post-tests were presented in tables, which helped to draw conclusions related to types of thinking, linguistic, cognitive and metacognitive strategies, emotional intelligences and to leadership and learning in general.